Design, modelling and testing of CMOS-MEMS switch - Ahmad, F. (Springer Science and Business Media Deutschland GmbH, 2021)
The Electro-Magnetic (EM) MEMS switches are playing an important role in our everyday life due to their high efficiency and system integrity. The design, modelling and testing of MEMS EM switch is presented in this research work. This chip-based MEMS switch is fabricated using 0.35Â Âµm Complementary Metal Oxide Semiconductor (CMOS) three metals-two poly technology, released i.e., post micromachining and packaged in Dual Inline package (DIP). The electromagnetic actuation-based CMOS-MEMS switch consists of two central coils joined to each other and two supporting beams. The two coils actuate in torsional mode by passing DC as well as AC current through coils. Switch is tested in static and dynamic modes. Actuation voltages of 68Â V are measured in the static mode, while in dynamic mode, voltages are 68Â mV. Finally, compared theoretical and experimental measurements. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.